The Scriptures and the scrolls : studies in honour of A.S. van der Woude on the occasion of his 65th birthday - Woude, A. S. van der.; García Martínez, Florentino.; Hilhorst, A.; Labuschagne, C. J. (Supplements to Vetus Testamentum,, 1992)
The present volume was compiled as a respectful tribute to A.S. van der Woude and presented to him on the occasion of his 65th birthday, which coincided with his retirement as professor of Old Testament and Intertestamental Studies at the University of Groningen, a chair he held for more than thirty years. The title of this Festschrift , The Scriptures and the Scrolls , reflects the two fields of study to which he has devoted his scholarly life, not only by doing research himself, but also by stimulating many of his colleagues to collaborate in publications initiated by him. The contributions, a mélange of studies covering the wide range of Van der Woude's interests, have been arranged according to the order: Hebrew Bible (following the sequence of the books), Apocrypha, Dead Sea Scrolls, and Rabbinic Tradition. From the Contents: E. Tov, '4QLevd (4Q26)' C.J. Labuschagne, ''You Shall not Boil a Kid in its Mother's Milk'. A New Proposal for the Origin of the Prohibition.' J.A. Emerton, 'The Translation of Isaiah 5,1.' J.T.A.G.M. van Ruiten, 'The Intertextual Relationship between Isa 11, 6-9 and Isa 65, 25.' W.A.M. Beuken, 'Isa 29, 15-24: Perversion Reverted.' W. McKane, 'Jeremiah 30, 1-3, Especially 'Israel.'' R.P. Carroll, 'Night without Vision. Micah and the Prophets.' C. van Leeuwen, 'The 'Northern One' in the Composition of Joel, 2, 19-27.' G. Wallis, A Note on Ps 45, 7aα.' M.J. Mulder, 'Does Canticles 6, 12 Make Sense?' B. Otzen, 'Michael and Gabriel. Angelological Problems in the Book of Daniel.' J.P.M. van der Ploeg, 'Some Remarks on a Newly Found Syriac Text of the Book of Judith.' A. Hilhorst, 'The Speech on Truth in 1 Esdras 4, 34-41.' P.R. Davies, 'Redaction and Sectarianism in the Qumran Scrolls.' M.A. Knibb, 'A Note on 4Q372 and 4Q390.' F. García Martínez, 'The Last Surviving Columns of 11QNJ.' G. Stemberger, 'The Maccabees in Rabbinic Tradition.' J. Neusner, 'How the Bavli Shaped Rabbinic Discourse: The Case of Sifra.' J.W. Rogerson, 'Writing the History of Israel in the 17th and 18th Centuries.' F. García Martínez, 'Bibliography of A.S. van der Woude.'